Trust and Type in Jesus Films: Playing with Expectations in Son of Man and Das neue Evangelium - Knowles, Melody D. (Biblical interpretation, 2025)
What types of media do we trust to tell the truth? How can cinematic technique promote or wear down such trust? As they re-tell ancient stories about Jesus, both Son of Man (Dornford-May, 2005) and Das neue Evangelium (Rau, 2020) trouble our assumptions as to the ability of different types of visual media to represent narrative accounts of the biblical past accurately. The films themselves are hybrid productions that incorporate into the Jesus film genre elements of musical theatre (Son of Man) and political protest (Das neue Evangelium). Such hybridity provides an effective context for exploring expectations of cinematic re-tellings of the past. As we are forced to make sense of what we see, we are newly aware of what we have come to expect. In addition, both films contrast visual media traditionally designated "high trust" such as documentaries and news reports with more "subjective" forms such as folk art and political protest, thus skewing our expectations for what truth-telling looks like and where it is found. This article looks at the ways in which Dornford-May and Rau interrogate traditional assumptions about Jesus films and filmic genre as they experiment with cinematic technique to comment on what we think we know.